Effects of intralipid and caffeic acid phenyl esther (CAPE) against hepatotoxicity and nephrotoxicity caused by glyphosate isopropylamine (GI). (April 2016) - Alp, Harun; Pinar, Neslihan; Dokuyucu, Recep; Kaplan, Ibrahim; Sahan, Mustafa; Senol, Serkan; Karakus, Ali; Yaldiz, Mehmet
This study was aimed to investigate the protective effects of caffeic acid phenyl esther (CAPE) and Intralipid (IL) against hepatotoxicity and nephrotoxicity caused by acute intoxication of glyphosate (N-phosphonomethyl)glycine) (GI) in rats. Forty-nine Wistar Albino rats were randomly divided into seven groups as: I, Control; II, Intralipid (IL) (18.6 mL/kg, orally); III, CAPE (10 µmol/kg, intraperitoneally); IV, GI (4 mg/kg/day, intraperitoneally); V, GI + IL; VI, GI+CAPE; and VII, GI + IL + CAPE. Total antioxidant status (TAS) and total oxidant status (TOS) levels were measured in serum samples. Tissues were analyzed with hematoxylin and eosin (H&E) staining protocol. Bcl-2, Bax, and caspase-3 were evaluated by immunohistochemical method. The results revealed that, in hepatic tissues, the TAS levels were lower and the TOS levels were higher in the GI group compared to other groups. In renal tissues, the TAS levels were significantly lower in the GI group than in the control, IL, CAPE, and GI + IL + CAPE groups. The TOS levels were significantly higher in the GI group than in the control group. Moreover, histopathological analysis revealed severe hepatotoxicity in the GI group. In the GI + CAPE + IL group, hepatotoxicity recovered significantly. Nephrotoxicity was also observed in the GI group and moderately reduced in the GI + CAPE group. Biochemical results were confirmed by histopathologic examination. The results also revealed that CAPE and IL, due to their antioxidant effects, have a decreasing effect against both hepatotoxicity and nephrotoxicity caused by GI. Therefore, CAPE and IL may function as potential agents for supportive therapy since they decrease organ damage, or may facilitate the therapeutic effects of the routine treatment of patients with GI poisoning.